Testing for stationarity in a cointegrated system - Robert M. Kunst (Institute for Advanced Studies (IHS), 2002)
In systems of variables with a specified or already identified cointegrating rank, stationarity of component variates can be tested by a simple restriction test. The implied decision is often in conflict with the outcome of unit root tests on the same variables. Using a framework of Bayes testing and decision contours, this paper searches for a solution to such conflict situations in sample sizes of empirical relevance. It evolves from the decision contour evaluations that the best test to be used jointly with a restriction test on self-cointegration is a modified version of the Dickey-Fuller test that accounts for the other system variables, whereas strictly univariate unit-root tests do not help much in the decision of interest.
Keywords: C11; C12; C15; C32; 330; Bayes test; unit roots; cointegration; decision contours; Kointegration; Unit Root Test; Statistischer Test; Theorie